Through the Looking Glass: Singapore’s First Customer Satisfaction Survey - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2008)
The Institute of Service Excellence (ISES) was established by the Singapore Management University (SMU) and Singapore’s Workforce Development Agency (WDA) in mid-2007. In April 2008, following a survey conducted across various sectors and subsectors, the Institute launched the nation’s first customer satisfaction index, known as the Customer Satisfaction Index of Singapore (CSISG). Singapore scored 68.7 out of 100 in the CSISG, lower than South Korea and the United States which scored 72 and 75 respectively.